Explaining Continuance Intention in Islamic Digital Banking: The Mediating Role of Digital Self-Efficacy Among Generation Z - Jafira Hasna Sajiddah; Harun Alrasyid; Irma Hidayati (El-Barka, 2026)
This study examines continuance intention toward Islamic digital banking among Generation Z, a segment that increasingly relies on digital financial services yet does not always maintain long-term usage. Despite the rapid growth of Islamic digital banking, there is a limited understanding of how cognitive, technological, and psychological factors jointly influence post-adoption behaviour. To address this gap, the study investigates the effects of Islamic financial literacy, information quality, and digital satisfaction on continuance intention, with digital self-efficacy serving as a mediating variable. The study contributes to the post-adoption literature by integrating Islamic financial literacy and digital self-efficacy into a unified framework for explaining sustainable usage behaviour in Islamic digital banking. Using a quantitative approach, data were collected from 205 Generation Z users of Islamic digital banking in Indonesia and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that Islamic financial literacy, information quality, and digital satisfaction significantly influence continuance intention and digital self-efficacy, with information quality emerging as the strongest predictor. Digital self-efficacy also mediates the relationships between these factors and continuance intention. These findings suggest that continuance intention in Islamic digital banking is shaped not only by technological performance but also by users’ knowledge and confidence in using digital financial services. Practically, Islamic financial institutions should enhance information quality, user experience, and Islamic financial literacy initiatives to encourage sustained engagement with Sharia-compliant digital banking services.